Pengaruh Pendapatan terhadap Usaha Ikan Hias Air Laut di PT. Indotama Putra Wahana Kota Bekasi Jawa Barat - Nurfadila Nurfadila; Mariam Mariam; Seniorita Seniorita (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
This study aims to analyze the effect of revenue on the ornamental fish business at PT. Indotama Putra Wahana. Revenue in this context refers to all income obtained by the company, both from export activities and from sales through online platforms such as Tokopedia. Business growth is defined as the increase in net profit, reflecting the sustainability and development of the company in running its operations. Therefore, it is important to analyze the contribution of income from both sources to the company’s success and growth. The data used in this study includes export revenue over the past six months and revenue from Tokopedia over the past four months. Net profit is calculated by subtracting total income from monthly operational costs. This study uses a quantitative approach with multiple linear regression analysis processed using SPSS software to obtain more accurate results. The research findings show that the ANOVA test resulted in an F value of 38.429 with a significance value of 0.007, indicating that both export revenue and Tokopedia revenue significantly affect business growth simultaneously. This suggests that both types of income play an important role in driving the company's growth. Additionally, the t-test shows that export revenue has a greater impact on business growth compared to Tokopedia revenue. The regression coefficient for export revenue is 0.987, while for Tokopedia revenue, it is 0.536. Overall, this study reveals that export revenue has a greater impact on the growth and sustainability of the ornamental fish business at PT. Indotama Putra Wahana. These findings provide deeper insight for the company to focus on export strategies to enhance net profit and ensure the sustainability of its business.